A holistic understanding of Mixed-Use theory in practice: analyzing the factors of success in three Kansas City mixed-use developments - Green, Jordan (Kansas State University, 2020)
Mixed-use development is one of the most popular modern development techniques in both practice and theory. Steeped in the rich history of traditional European city building and forefront to famous planning frameworks such as new urbanism and transit-oriented development, mixed-use theory is seen as a way of improving community vibrancy, walkability, density, and more. However, due to the complexities inherent in the planning, design, and construction phases—as well as a host of other difficulties not faced by single-use developments—mixed-use development is a much riskier endeavor than other types of development. Further complicating these issues is the relative newness of this type of development in the modern real estate and planning worlds. This has led to a discrepancy in the literature between the planning, design, and development factors that the mixed-use theorists prescribe as beneficial. This affects how mixed-use developments are developed and operated in actuality. This research project begins to build the connection between theory and practice by first identifying the factors theorized in the literature as being beneficial to a mixed-use development’s success. It then describes and analyzes to what extent three mixed-use developments in the Kansas City Metropolitan Area—Park Place, Prairiefire, and Zona Rosa—demonstrate these factors of success. In doing so, this research diminishes the disconnect between theory and practice for successful mixed-use development in the Kansas City Metro context and could begin to inform a framework for less risky and more successful future Kansas City mixed-use developments.
Keywords: Planning; Mixed-use; Development